Environmental and economic impact of using increased fresh gas flow to reduce carbon dioxide absorbent consumption in the absence of inhalational anaesthetics. (November 2020) - Zhong, George; Abbas, Ali; Jones, Joseph; Kong, Sarah; McCulloch, Tim
Abstract: Background: Increasing fresh gas flow (FGF) to a circle breathing system reduces carbon dioxide (CO2 ) absorbent consumption. We assessed the environmental and economic impacts of this trade-off between gas flow and absorbent consumption when no inhalational anaesthetic agent is used. Methods: A test lung with fixed CO2 inflow was ventilated via a circle breathing system of an anaesthetic machine (Dräger Primus or GE Aisys CS 2 ) using an FGF of 1, 2, 4, or 6 L min −1 . We recorded the time to exhaustion of the CO2 absorbent canister, defined as when inspired partial pressure of CO2 exceeded 0.3 kPa. For each FGF, we calculated the economic costs and the environmental impact associated with the manufacture of the CO2 absorbent canister and the supply of medical air and oxygen. Environmental impact was measured in 100 yr global-warming potential, analysed using a life cycle assessment 'cradle to grave' approach. Results: Increasing FGF from 1 to 6 L min −1 was associated with up to 93% reduction in the combined running cost with minimal net change to the 100 yr global-warming potential. Most of the reduction in cost occurred between 4 and 6 L min −1 . Removing the CO2 absorbent from the circle system, and further increasing FGF to control CO2 rebreathing, afforded minimal further economic benefit, but more than doubled the global-warming potential. Conclusions: In the absence of inhalational anaesthetic agents, increasing FGF to 6 L min −1 reduces running cost compared with lower FGFs, with minimal impact to the environment.